Fatty Acids as Aminoglycoside Antibiotic Adjuvants Against Staphylococcus aureus - Park, Sunyoung; Lee, Jin-Hyung; Kim, Yong-Guy; Hu, Liangbin; Lee, Jintae (Frontiers in Microbiology, 2022)
Fatty acids have diverse functions in the vast majority of cells. At high doses, they act as antimicrobials while, at low doses, they exhibit antibiofilm and antivirulence activities. In this study, the synergistic antibacterial and antibiofilm activities of 30 fatty acids and 11 antibiotics were investigated against methicillin-sensitive and methicillin-resistant Staphylococcus aureus strains. Of the 15 saturated and 15 unsaturated fatty acids examined, 16 enhanced the antibacterial activity of tobramycin. Combinatorial treatment with myristoleic acid (the most active) at 10 µg/ml and tobramycin at 10 µg/ml decreased cell survival by > 4 log as compared with tobramycin treatment alone. Notably, aminoglycoside antibiotics, such as tobramycin, kanamycin, gentamicin, and streptomycin exhibited antimicrobial synergy with myristoleic acid. Co-treatment with myristoleic acid and antibiotics markedly decreased biofilm formation. Interestingly, co-treatment with tobramycin and myristoleic acid induced a reduction in S. aureus cell size. These results suggest that fatty acids, particularly myristoleic acid, can be used as aminoglycoside antibiotic adjuvants against recalcitrant S. aureus infections.